2014
DOI: 10.1155/2014/465054
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Screening of Virulence Genes in Extraintestinal PathogenicEscherichia coliIsolated from Human Blood Culture in Brazil

Abstract: Extraintestinal pathogenic Escherichia coli (ExPEC) is one of the main etiological agents of bloodstream infections caused by Gram-negative bacilli. In the present study, 20 E. coli isolates from human hemocultures were characterized to identify genetic features associated with virulence (pathogenicity islands markers, phylogenetic group, virulence genes, plasmid profiles, and conjugative plasmids) and these results were compared with commensal isolates. The most prevalent pathogenicity island, in strains from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
39
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 33 publications
12
39
2
Order By: Relevance
“…With respect to median PAIs ( Figure 3A and B), there was very close convergence between clinical and environmental isolates. These results substantiate the probability that environmental isolates are not commensals, which came in accordance with Koga et al (39).…”
Section: Discussionsupporting
confidence: 92%
“…With respect to median PAIs ( Figure 3A and B), there was very close convergence between clinical and environmental isolates. These results substantiate the probability that environmental isolates are not commensals, which came in accordance with Koga et al (39).…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of hlyA gene encoding a toxin implicated in tissue damage and dysfunction of local immune responses was found more frequently in phylogenetic group B2. The distribution of this gene in our isolates is in agreement with other reports (21,22). The prevalence of genes encoding the aerobactin and siderophore receptors (iucD and iroN), which confers the ability to take up iron, among isolates belonging to phy-Int J Enteric Pathog.…”
Section: Discussionsupporting
confidence: 92%
“…Our vaccine will diminish, if not ultimately eliminate, pathogenic E. coli with minimal cross-reactivity with the healthy flora, because IroN and IutA antigens targeted within this vaccine are more prevalent among ExPEC than commensal E. coli [4042]. Regarding the ECP antigen, since it has been shown that in in vitro conditions mimicking the in vivo situation, only virulent E. coli highly produced ECP, whereas commensal E. coli did not [43]; as our vaccine will only target ECP-expressing E. coli in vivo , it would not have effect on non-ECP-expressing commensal E. coli .…”
Section: Discussionmentioning
confidence: 99%